Determinants of European tourism demand in a demographic ageing society - Serra, Jaime (2017)
This study identifies the senior European tourists determinants that explained their decisions to go on holidays. The empirical study was conducted among European tourists by applying a logit model. The model intends to explain the determinants related to the decision to go on holidays since the probability of a senior European tourist taking holidays in a country depends on a mix of motives as previous travel experience and demographic characteristics. Policy and theoretical implications are derived for contributing to the discussion between demographic variables and tourism demand choice patterns.